2009
DOI: 10.1016/j.jep.2009.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive and endothelium-independent vasorelaxant effects of methanolic extract from Curcuma longa L. in rats

Abstract: These results demonstrate the hypotensive and bradycardic effects of CLME, as well as its potent vasodilation of rat mesenteric arteries. These effects, may in part, be due to the inhibition of extracellular Ca(2+) influx and/or inhibition of intracellular Ca(2+) mobilization from Phe-sensitive stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…In a previous study, Sasaki et al, (2003) reported the endothelium-independent vasomotional effects of five Curcuma drugs (Curcuma longa inclusive) in isolated rat aorta. Recently, it was demonstrated that CL lowers arterial blood pressure and heart rate in rats, probably due to the blockade of extracellular Ca 2+ influx and, the inhibition of intracellular Ca 2+ release for inositol-1,4,5-triphosphate (IP3) sensitive stores (Adaramoye et al, 2008). These results provide enough background to explore the involvement of the Na + -Ca 2+ exchanger in the vasorelaxant effects induced by CL in isolated rat superior mesenteric arteries.…”
Section: Introductionmentioning
confidence: 91%
“…In a previous study, Sasaki et al, (2003) reported the endothelium-independent vasomotional effects of five Curcuma drugs (Curcuma longa inclusive) in isolated rat aorta. Recently, it was demonstrated that CL lowers arterial blood pressure and heart rate in rats, probably due to the blockade of extracellular Ca 2+ influx and, the inhibition of intracellular Ca 2+ release for inositol-1,4,5-triphosphate (IP3) sensitive stores (Adaramoye et al, 2008). These results provide enough background to explore the involvement of the Na + -Ca 2+ exchanger in the vasorelaxant effects induced by CL in isolated rat superior mesenteric arteries.…”
Section: Introductionmentioning
confidence: 91%
“…Medicinal plants contain several classes of bioactive compounds such as polyphenols, alkaloids and terpenes (Oliveira et al, 1996;Barbosa-Filho et al, 2000;Adaramoye et al, 2009). Among the pharmacological activities of compounds isolated from medicinal drugs on the cardiovascular system are calcium antagonism, NO release, antioxidant and others (Guedes et al, 2004;Ribeiro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, C. mukul resin was extracted using petroleum ether, 16 S. reticulata root using water, 17 bark of T. arjuna 18 and rhizome of C. longa using methanol. 19 Approximately, 20 g of each powder was extracted with 150 mL of respective solvent using a magnetic stirrer for 72 h; changing solvent every 24 h. Each time the supernatants obtained by centrifugation were collected. Finally the supernatants were pooled, concentrated and evaporated to dryness in a water bath.…”
Section: Hptlc Fingerprintingmentioning
confidence: 99%